Silicon-containing apatite fiber scaffolds with enhanced mechanical property express osteoinductivity and high osteoconductivity. Issue 2 (3rd April 2019) - Yamada, Y.; Inui, T.; Kinoshita, Y.; Shigemitsu, Y.; Honda, M.; Nakano, K.; Matsunari, H.; Nagaya, M.; Nagashima, H.; Aizawa, M.
ABSTRACT: We began this study by synthesizing apatite fibers (AFs) and silicon-containing apatite fibers (Si-AFs) using a homogeneous precipitation method. Next, we have successfully fabricated three-dimensional apatite fiber scaffolds (AFSs) and silicon-containing apatite fiber scaffolds (Si-AFSs) using the above the AFs and Si-AFs, respectively. Finally, we successfully enhanced the mechanical properties of the scaffolds using carbon beads (CBs) with diameters of 20 μm and 150 μm, and conducted uniaxial pressing of the green compacts. These were named "AFS100, " "AFS300, " "Si-AFS100, " and "Si-AFS300" based on the AF (or Si-AF)/CB ratio. In the study, these scaffolds with enhanced mechanical property were implanted into porcine tibia, muscle and fat, and their osteoconduction and osteoinduction were examined. The bone-formation rates of Si-AFS100 and Si-AFS300 were higher than those of AFS100 and AFS300, while the bone-formation rates of AFS100 and Si-AFS100, were higher than those of AFS300 and Si-AFS300. These results indicated that addition of Si and controlled porosity may promote osteoconduction. Furthermore, AFS100 and Si-AFS100 exhibited osteoinductivity in muscle in the absence of osteoblasts. In conclusion, Si-AFS100 with enhanced mechanical properties has high osteoconductivity and osteoinductivity and can be expected to be used as a scaffold material and next-generation artificial bone filler for promoting bone formation.